Evaluating the effect of metronidazole plus amoxicillin‐clavulanate versus amoxicillin‐clavulanate alone in canine haemorrhagic diarrhoea: a randomised controlled trial in primary care practice. (7th June 2018) - Ortiz, V.; Klein, L.; Channell, S.; Simpson, B.; Wright, B.; Edwards, C.; Gilbert, R.; Day, R.; Caddy, S. L.
Abstract : Objectives: To investigate the benefit of supplementing amoxicillin‐clavulanic acid therapy with metronidazole in dogs presenting to a primary care veterinary practice with severe haemorrhagic diarrhoea. Materials and Methods: Prospective randomised blinded trial on dogs presenting with haemorrhagic diarrhoea of less than 3 days duration to a primary care veterinary hospital and also requiring intravenous fluid therapy. Cases were randomised to receive either metronidazole or saline, in addition to standard supportive therapy consisting of amoxicillin‐clavulanic acid, intravenous fluid therapy, buprenorphine and omeprazole. Treatment efficacy was measured by duration of hospitalisation and daily scoring of disease severity. Results: Thirty‐four cases successfully completed the trial. There was no significant difference in hospitalisation time between treatment groups (mean for dogs receiving metronidazole was 29.6 hours and for controls was 26.3 hours) nor in daily clinical scores. Clinical Significance: This study strongly suggests that addition of metronidazole is not an essential addition to amoxicillin‐clavulanic acid therapy for treatment of severe cases of haemorrhagic diarrhoea in dogs.